PRINSIP KE HATI-HATIAN DALAM PERJANJIAN KREDIT MELALUI E-COMMERCE (AKULAKU) - Dwi Ajeng Ayu P; Dipo Wahyoeono (Gapenas Publisher, 2022)
Along with current developments, providing support in a wider variety of business networks without limits, accessing the internet is not limited to accessing information only through available media, but can also be used as a means of trading sales transactions with various existing market place platforms, as well as a network that wide to no limit of time and place. In its implementation of online applications, there are still many obstacles and problems that occur, as a result of the occurrence of a bad system from the banking system, namely superiors or actors who often behave badly and pay less attention to the principle of prudence in doing business. The fundamental statement that is used as a benchmark by a person or group of people is the principle in carrying out an action and a statement of their thoughts, one of the principles contained in the law is the principle of prudence which is the principle of environmental law that regulates which behavior should be avoided. Then the formulation of the problem that will be used is 1. How to apply the precautionary principle in the e-commerce credit system (Akulaku)? 2. What are the legal consequences if you do not apply the principle of prudence in credit agreements? The research method used is normative legal research in order to find legal rules by carrying out 2 (two) approaches, namely the statutory approach and the conceptual approach. 5 C, Character Value, Ability Value, Capital Value, Collateral Value and Value on the debtor's business prospects, in making a credit purchase if there is a violation, it will result in legal consequences and the party who violates it will be subject to a maximum fine of Rp. 100,000,000,000